Indonesia - Amelia Mardhatillah Sipahutar; Zulpahmi Lubis (Universitas Muhammadiyah Ponorogo, 2026)
The discovery of nine processed food products containing pork (porcine) elements in April 2025, some of which had already been halal certified, caused public concern and raised questions regarding the effectiveness of the halal certification system and the legal protection of consumers. This study aims to analyze the roles and responsibilities of the Regional Office of the Halal Product Assurance Organizing Agency (UPT Badan Penyelenggara Jaminan Produk Halal/BPJPH) of North Sumatra and LPPOM MUI of North Sumatra in ensuring the authenticity of halal food products, as well as to examine the forms of legal protection provided to consumers over halal-certified products that are proven to contain porcine elements. The theoretical framework of this study is based on the concepts of legal protection, consumer protection, and halal product assurance, referring to Law Number 33 of 2014 concerning Halal Product Assurance and Law Number 8 of 1999 concerning Consumer Protection. This research employs a normative-empirical legal research method, which combines the study of statutory regulations with empirical data obtained through interviews and observations conducted at the UPT BPJPH and LPPOM MUI of North Sumatra. The results show that weak post-certification supervision and the lack of good faith among business actors are the main factors contributing to violations of halal integrity. Legal protection for consumers is implemented through preventive measures in the form of socialization, education, internal audits, and periodic supervision, as well as repressive measures in the form of revocation of halal certificates, withdrawal of products from circulation, and the imposition of administrative sanctions on business actors. This study emphasizes the need to strengthen supervisory functions, enforce sanctions consistently, and enhance inter-institutional coordination in order to ensure legal certainty and effective consumer protection.